Determinants for the Adoption of Educational Technology in Zimbabwean Vocational Training Centres - DHOKURA, EUNICE; TSVERE, MARIA; MUNIKWA, SIMBARASHE (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2024)
This study centres on factors influencing educational technology (EdTech) adoption in vocational training programmes with a primary and particular focus on Zimbabwean vocational training centres (VTCs). The main objective of the study was to determine and critically examine the factors influencing EdTech adoption in vocational training programmes. The study identified the following factors influencing EdTech adoption in these programmes: participant level factors examined include demographics, computer skills and motivation and institutions level factors at very different academic levels. Quantitative data were gathered from students at VTCs, whilst qualitative data were obtained from lecturers and staff, also at VTCs, to complement the quantitative data. The research instruments used were questionnaires, interview guides and observation guides. Both probability and non-probability samples were used. Thus, the target population for this study consisted of 3 500 participants drawn from five VTCs. Research has concluded that two beliefs, perceived usefulness and perceived ease of use have been identified as important user acceptance criteria. The study also found out that participant‘s desire for vocational learning may also influence motivation and academic achievement. The study recommends that investing in education is a potent means that could be explored to fast-track technological progress, economic growth and boosting citizens' capacities and bridging the gap of educational learning and opportunities between learners from different economic backgrounds.